Natural regeneration on clear cuts in Southern Sweden - Jónsson, Jón Ásgeir (2016)
The forests of Europe have seen a dramatic shift in structure, species composition and area coverage in the last centuries. Large areas previously covered by a mixed broad-leaved forest are now used for agriculture or other land uses. Additionally the forest management saw changes with the optimization of wood production as a main goal, using monocultures of conifers and clear cutting becoming prevalent. This development, although so far economically successful, has major disadvantages. With the decline of suitable habitat, the biodiversity connected to broad-leaved ecosystems is now under threat. Furthermore frequent storm falls and pest outbreaks have hit monocultures severely and the uncertain effects of climate change on individual tree species has reinvigorated the economic argument for risk spreading and moving back to the more resilient mixed forests system. Thus, effective and preferably inexpensive methods are needed to restore preferred mixed broad-leaved forests in desired locations. This paper will cover a research conducted on clear cuts that were made in 2011 in southern Sweden, previously covered with planted stands of Norway spruce, Picea abies. The aim was to examine the effects of soil treatment, fencing and distance from broad-leaved forest on the natural regeneration of woody species and on the ground vegetation. All naturally regenerated tree saplings that had reached a height of 30 cm were recorded and the ground vegetation was assessed with a cover estimate. The significance of the treatments on the quantity and height of saplings and the flora coverage was evaluated with a General linear model. Five species represented 96% of the recorded tree regeneration, Betula spp. (B. pendula, B. pubescens), Salix caprea, Pinus sylvestris and Populus tremula. Statistical analysis focused on these species. The natural regeneration produced on average ca 4500 trees/ha. Fencing had a significant positive effect on the height of all the four most numerous species (Betula ssp., S. caprea, P. sylvestris, P. tremula) and on the P. sylvestris regeneration. Soil scarification increased the quantity of S. caprea and P. sylvestris. Notably, distance from a broadleaved forest had no significant impact on height or quantity of overall individuals or within species. The models were most suited to predict the observed variance for S. caprea and P. sylvestris (R-sq. ~50-68%) while least apt at explaining the variance in Betula ssp. (R-sq. ~26-36%). The results indicate that distance from broad-leaved forest is not an important factor in the early stages of natural forest regeneration. Pioneer tree species dominate the clear cuts and saplings of noble broadleaves are either not present or very scarce. Unstable seed production, short seed dispersal and unfavourable conditions on new clear cuts might limit the colonization of noble broadleaves and connected ground flora. Though fencing and soil treatment had a positive effect on number and height of individuals of some species, the plots without any treatment (no fence, no soil treatment) managed to produce roughly 3000 seedlings/ha containing a mix of species. The ratio of P. sylvestris and S. caprea present is, however, much lower without treatment. These species are important for forest biodiversity and their increased density alone might justify fencing. Future research is needed to document the progression and what species will prevail after this initial colonization phase.